First days of martial law in Nowa Huta - KAPUSTA, PIOTR (Journal of Education Culture and Society, 2020)
The theme of my work is related to the thirtieth anniversary of the introduction of mar-tial law in Poland on the 13th December 1981 by General Wojciech Jaruzelski. It concerns one of the largest sites of resistance in the country – Nowa Huta. I have presented what the arrest of the opposition activist in Nowa Huta looked like on the night of 12/13 December 1981 and I have presented the course of strike and its repression in the largest workplace in Cracow – in the Vladimir Lenin Steelworks in Nowa Huta.